IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE ON RECRUITMENT PROCESS: A LITERATURE REVIEW - Nababan, Boy Chandra; Praseyta, Muhammad Dimas; Adelia, Nurul; Dalimunthe, Ritha F. (Cahaya Ilmu Bangsa, 2024)
Artificial intelligence (AI) has become a transformative force across various fields, including recruitment. Its integration into hiring processes has redefined how organizations identify, evaluate, and retain talent. By offering enhanced efficiency, reduced biases, and better decision-making, AI presents significant advantages in recruitment. The methodology employed in this study is a descriptive qualitative approach, where researchers gather data from various literature sources and utilize qualitative methods, as the data collected is presented in the form of words or descriptions. This literature review examines the implementation of AI in recruitment, focusing on its benefits, risks and ethical concerns, and also practical implications and strategic insights.as the result, AI for recruitment tools provide notable advantages, such as increased efficiency, cost reduction, and better candidate matching. However, they also pose challenges, including algorithmic bias, concerns over job security, and issues related to data privacy.